Economic Calendar Of Karakalpaks (Zien Journal of Social Sciences and Humanities, 2022)
From time immemorial, people have used calendars for household chores and in everyday life. Calendars are defined as the time of gatherings, holidays, and religious ceremonies. According to SI Ojegova's explanatory dictionary, "Calendar" is a system for determining large time steps. The calendar is a computational system for determining the dates of these numbers